3+2+( (2^27·3^35)²:(2^51·3^69)-4^17:2^33+35 )
Răspunsuri la întrebare
Răspuns de
0
3+2+( (2^27·3^35)²:(2^51·3^69)-4^17:2^33+35)
=
=5+( (2^54·3^70):(2^51·3^69)-2^34:2^33+35 ) =
=5+( 2^3·3-2+35 ) =
=5+24-2+35=62
=5+( (2^54·3^70):(2^51·3^69)-2^34:2^33+35 ) =
=5+( 2^3·3-2+35 ) =
=5+24-2+35=62
Bubulyna123:
nu e corect
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă